Endovascular Aneurysm Sealing for the Treatment of Ruptured Abdominal Aortic Aneurysms. (June 2015) - de Bruin, Jorg L.; Brownrigg, Jack R. W.; Karthikesalingam, Alan; Patterson, Benjamin O.; Holt, Peter J. E.; Hinchliffe, Robert J.; Morgan, Robert A.; Loftus, Ian M.; Thompson, Matthew M.
Purpose: To assess the feasibility and report preliminary results of ruptured abdominal aortic aneurysm (rAAA) repair with endovascular aneurysm sealing (EVAS), a novel therapeutic alternative whose feasibility has not been established in rAAAs due to the unknown effects of the rupture site on the ability to achieve sealing.Case Report: Between December 2013 and April 2014, 5 patients (median age 71 years, range 57–90; 3 men) with rAAAs were treated with the Nellix EVAS system at a single institution. Median aneurysm diameter was 70 mm (range 67–91). Aneurysm morphology in 4 of the 5 patients was noncompliant with instructions for use (IFU) for both EVAS and standard stent-grafts; the remaining patient was outside the IFU for standard stent-grafts but treated with EVAS under standard IFU for the Nellix system. Median Hardman index was 2 (range 0–3). Two patients died of multiorgan failure after re-laparotomy and intraoperative cardiac arrest, respectively. Among survivors, all devices were patent with no signs of endoleak or failed aneurysm sac sealing at 6 months (median follow-up 9.2 months).Conclusion: EVAS for the management of infrarenal rAAAs appears feasible. The use of EVAS in emergency repairs may broaden the selection criteria of the current endovascular strategy to include patients with more complex aneurysm morphology.